2005
DOI: 10.1111/j.1472-8206.2005.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human cytochrome P450 isoenzymes involved in the metabolism of vinorelbine

Abstract: Vinorelbine (VRL) (IV Navelbine) is a semi-synthetic vinca alkaloid, used in therapeutics for the treatment of non-small-cell lung cancer and advanced breast cancer. The aim of this study was to characterize the cytochrome P450 (CYP) isoenzymes involved in VRL metabolism. VRL was incubated at 1.28 x 10(-5) m for 90 min with human hepatic microsomes prepared from 14 donors (one woman and 13 men aged from 27 to 76 years old) and characterized for CYP1A2, CYP2D6, CYP2E1 and CYP3A4 activities. A four-combined-appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…This was consistent with in vitro studies showing that CYP3A4 was the main isoenzyme involved in the metabolism of VRL [9,23].…”
Section: Discussionsupporting
confidence: 93%
“…This was consistent with in vitro studies showing that CYP3A4 was the main isoenzyme involved in the metabolism of VRL [9,23].…”
Section: Discussionsupporting
confidence: 93%
“…Unchanged vinorelbine was the major compound recovered in faeces (30 -50% of the dose). All metabolites were formed trough cytochrome P450 CYP 3A4 except 4-O-deacetylvinorelbine [21,22]. All the metabolites but one -4-O-deacetylvinorelbine -are inactive.…”
Section: Metabolismmentioning
confidence: 99%
“…Two articles have reported the identification of the CYP involved in the in vitro metabolism of vinorelbine 21,22 . Kajita et al 21 first observed additional chromatographical peaks corresponding to polar metabolites of unknown structure after the incubation of vinorelbine (0.5 μM) using human liver microsomes and recombinant CYP3A4.…”
Section: Human Molecular Determinants Of Catharanthus Alkaloids Pharmmentioning
confidence: 99%